Jump to content
Wikipedia The Free Encyclopedia

Factor theorem

From Wikipedia, the free encyclopedia
This is an old revision of this page, as edited by S243a (talk | contribs) at 11:54, 18 December 2010 (Formal version ). The present address (URL) is a permanent link to this revision, which may differ significantly from the current revision .Revision as of 11:54, 18 December 2010 by S243a (talk | contribs) (Formal version )
This article does not cite any sources . Please help improve this article by adding citations to reliable sources. Unsourced material may be challenged and removed.
Find sources: "Factor theorem" – news · newspapers · books · scholar · JSTOR
(November 2009) (Learn how and when to remove this message)

In algebra, the factor theorem is a theorem linking factors and zeros of a polynomial. It is a special case of the polynomial remainder theorem.

The factor theorem states that a polynomial f ( x ) {\displaystyle f(x)} {\displaystyle f(x)} has a factor ( x k ) {\displaystyle (x-k)} {\displaystyle (x-k)} if and only if f ( k ) = 0 {\displaystyle f(k)=0} {\displaystyle f(k)=0}.

Factorization of polynomials

Two problems where the factor theorem is commonly applied are those of factoring a polynomial and finding the roots of a polynomial equation; it is a direct consequence of the theorem that these problems are essentially equivalent.

The factor theorem is also used to remove known zeros from a polynomial while leaving all unknown zeros intact, thus producing a lower degree polynomial whose zeros may be easier to find. Abstractly, the method is as follows:

  1. First "guess" a zero a {\displaystyle a} {\displaystyle a} of the polynomial f {\displaystyle f} {\displaystyle f}. (In general, this can be very hard, but math textbook problems that involve solving a polynomial equation are often designed so that some roots are easy to discover.)
  2. Use the factor FML theorem to conclude that ( x a ) {\displaystyle (x-a)} {\displaystyle (x-a)} is a factor of f ( x ) {\displaystyle f(x)} {\displaystyle f(x)}.
  3. Compute the polynomial g ( x ) = f ( x ) / ( x a ) {\displaystyle g(x)=f(x){\big /}(x-a)} {\displaystyle g(x)=f(x){\big /}(x-a)}, for example using polynomial long division.
  4. Conclude that any root x a {\displaystyle x\neq a} {\displaystyle x\neq a} of f ( x ) = 0 {\displaystyle f(x)=0} {\displaystyle f(x)=0} is a root of g ( x ) = 0 {\displaystyle g(x)=0} {\displaystyle g(x)=0}. Since the polynomial degree of g {\displaystyle g} {\displaystyle g} is one less than that of f {\displaystyle f} {\displaystyle f}, it is "simpler" to find the remaining zeros by studying g {\displaystyle g} {\displaystyle g}.

An example

You wish to find the factors of

x 3 + 7 x 2 + 8 x + 2. {\displaystyle x^{3}+7x^{2}+8x+2.} {\displaystyle x^{3}+7x^{2}+8x+2.}

To do this you would use trial and error to find the first x value that causes the expression to equal zero. To find out if ( x 1 ) {\displaystyle (x-1)} {\displaystyle (x-1)} is a factor, substitute x = 1 {\displaystyle x=1} {\displaystyle x=1} into the polynomial above:

x 3 + 7 x 2 + 8 x + 2 = ( 1 ) 3 + 7 ( 1 ) 2 + 8 ( 1 ) + 2 {\displaystyle x^{3}+7x^{2}+8x+2=(1)^{3}+7(1)^{2}+8(1)+2} {\displaystyle x^{3}+7x^{2}+8x+2=(1)^{3}+7(1)^{2}+8(1)+2}
= 1 + 7 + 8 + 2 {\displaystyle =1+7+8+2} {\displaystyle =1+7+8+2}
= 18. {\displaystyle =18.} {\displaystyle =18.}

As this is equal to 18 and not 0 this means ( x 1 ) {\displaystyle (x-1)} {\displaystyle (x-1)} is not a factor of x 3 + 7 x 2 + 8 x + 2 {\displaystyle x^{3}+7x^{2}+8x+2} {\displaystyle x^{3}+7x^{2}+8x+2}. So, we next try ( x + 1 ) {\displaystyle (x+1)} {\displaystyle (x+1)} (substituting x = 1 {\displaystyle x=-1} {\displaystyle x=-1} into the polynomial):

( 1 ) 3 + 7 ( 1 ) 2 + 8 ( 1 ) + 2. {\displaystyle (-1)^{3}+7(-1)^{2}+8(-1)+2.} {\displaystyle (-1)^{3}+7(-1)^{2}+8(-1)+2.}

This is equal to 0 {\displaystyle 0} {\displaystyle 0}. Therefore x = ( 1 ) {\displaystyle x=(-1)} {\displaystyle x=(-1)}, which is to say x + 1 {\displaystyle x+1} {\displaystyle x+1}, is a factor, and 1 {\displaystyle -1} {\displaystyle -1} is a root of x 3 + 7 x 2 + 8 x + 2. {\displaystyle x^{3}+7x^{2}+8x+2.} {\displaystyle x^{3}+7x^{2}+8x+2.}

The next two roots can be found by algebraically dividing x 3 + 7 x 2 + 8 x + 2 {\displaystyle x^{3}+7x^{2}+8x+2} {\displaystyle x^{3}+7x^{2}+8x+2} by ( x + 1 ) {\displaystyle (x+1)} {\displaystyle (x+1)} to get a quadratic, which can be solved directly, by the factor theorem or by the quadratic equation.

( x 3 + 7 x 2 + 8 x + 2 ) ( x + 1 ) = x 2 + 6 x + 2 {\displaystyle {(x^{3}+7x^{2}+8x+2) \over (x+1)}=x^{2}+6x+2} {\displaystyle {(x^{3}+7x^{2}+8x+2) \over (x+1)}=x^{2}+6x+2}

and therefore ( x + 1 ) {\displaystyle (x+1)} {\displaystyle (x+1)} and x 2 + 6 x + 2 {\displaystyle x^{2}+6x+2} {\displaystyle x^{2}+6x+2} are the factors of x 3 + 7 x 2 + 8 x + 2. {\displaystyle x^{3}+7x^{2}+8x+2.} {\displaystyle x^{3}+7x^{2}+8x+2.}

Formal version

Let f {\displaystyle f} {\displaystyle f} be a polynomial with complex coefficients, and a {\displaystyle a} {\displaystyle a} be in an integral domain (e.g. a C {\displaystyle a\in \mathbb {C} } {\displaystyle a\in \mathbb {C} }). Then f ( a ) = 0 {\displaystyle f(a)=0} {\displaystyle f(a)=0} if and only if f ( x ) {\displaystyle f(x)} {\displaystyle f(x)} can be written in the form f ( x ) = ( x a ) g ( x ) {\displaystyle f(x)=(x-a)g(x)} {\displaystyle f(x)=(x-a)g(x)} where g ( x ) {\displaystyle g(x)} {\displaystyle g(x)} is also a polynomial. g {\displaystyle g} {\displaystyle g} is determined uniquely.

This indicates that those a {\displaystyle a} {\displaystyle a} for which f ( a ) = 0 {\displaystyle f(a)=0} {\displaystyle f(a)=0} are precisely the roots of f ( x ) {\displaystyle f(x)} {\displaystyle f(x)}. Repeated roots can be found by application of the theorem to the quotient g {\displaystyle g} {\displaystyle g}, which may be found by polynomial long division.

AltStyle によって変換されたページ (->オリジナル) /